Exploring the Effects of Price, Service Quality, and Promotion on Customer Satisfaction among TikTok Shop Student Users in Medan City - Kevin Putra Leonardo Nababan; Sinta Amanda br bangun; Risca Atania Br Gurusinga; Ricky Rafii Ritonga; Zenni Riana (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2026)
The rapid growth of social commerce has transformed consumer shopping behavior, particularly among university students who actively use digital platforms such as TikTok Shop. This study aims to examine the effects of price, service quality, and promotion on customer satisfaction among active TikTok Shop student users in Medan City. A quantitative approach was employed, with data collected from 100 respondents selected through purposive sampling. The data were analyzed using multiple linear regression to determine both partial and simultaneous effects among the variables. The findings reveal that price has a positive and significant effect on customer satisfaction, as indicated by a t-value of 3.285 and a significance value of 0.009. Service quality also has a positive and significant effect on customer satisfaction, with a t-value of 3.697 and a significance value of 0.000, making it the most dominant variable in this study. Furthermore, promotion has a positive and significant effect on customer satisfaction, with a t-value of 3.027 and a significance value of 0.003. These results indicate that affordable and appropriate pricing, responsive service, and attractive promotional offers play important roles in shaping students’ satisfaction with TikTok Shop. Simultaneously, price, service quality, and promotion have a positive and significant effect on customer satisfaction, as shown by an F-value of 29.674 and a significance value of 0.000. The coefficient of determination shows that the three independent variables explain 48.1% of the variation in customer satisfaction, while the remaining 51.9% is influenced by other factors not examined in this study. The descriptive analysis further indicates that students’ perceptions of price, service quality, promotion, and customer satisfaction are generally in the high category.